THE APPLICATION OF AI (ARTIFICIAL INTELLIGENCE)-BASED LEARNING MEDIA TO SUPPORT THE DIGITAL LITERACY OF 21ST CENTURY STUDENTS IN ELEMENTARY SCHOOLS - Dahlan, Taufiqulloh; Asna, Hilmiatun; Pratama , Yoga; Nur Fadillah, Nadil; Salsabila, Aulia; Nur Awaliah, Hanifah (International Journal of Multidisciplinary Research and Literature, 2026)
Digital literacy is a fundamental competency for students in the 21st century; however, the digital literacy skills of elementary school students in Indonesia remain low and suboptimal in addressing the challenges of the digital era. This research aims to explore in depth the application of artificial intelligence (AI)-based learning media to support the development of digital literacy among elementary school students in the context of 21st-century learning. The study employs a qualitative case study design to examine three elementary schools in urban, semi-urban, and rural areas that have implemented AI-based learning media. The research participants included 18 teachers in grades 4-6, 9 principals, and 36 students, all selected purposively. Data were collected through in-depth interviews, participatory observations, focus group discussions, and documentation over six months. Data analysis uses a thematic, inductive-iterative approach to identify emerging themes and patterns. The results of the study identified five main themes: (1) personalisation of learning increases student engagement and understanding of the concept of digital literacy; (2) AI media facilitates adaptive learning according to individual learning styles and speeds; (3) interactive and gamification features increase motivation and learning independence; (4) implementation challenges include infrastructure limitations, teachers' digital competence, and the balance between technology and social interaction; (5) Success factors include school management support, ongoing teacher training, and user-friendly media design. The research provides an in-depth understanding of the dynamics of AI media applications in digital literacy learning, offering practical recommendations for effective implementation in primary schools that account for socio-cultural contexts and diverse infrastructure conditions